THE ROLE OF ABDURRAHMAN WAHID IN CREATING ISLAMIC POST-TRADITIONALIST PARADIGM IN INDONESIA - Tajuddin, Muhammad Saleh (Jurnal Adabiyah, 2019)
This writing describes Abdurrahman Wahid’s thought and his influence in creating a new paradigm of thought among the new generation of Nahdlatul Ulama (NU) organization in Indonesia. This writing applies qualitative techniques through library and field research. Primary data are collected through observation, interviews, and documentation, while secondary data are collected through textbooks, journals, and the internet. The data are analyzed by descriptive analysis. NU organization is known as a traditionalist Islamic organization vis a vis an Islamic modernist organization Muhammadiyah. Wahid wants Muslim integrity to become a good community, such as tolerate and respect other people. Every Muslim has to respect other people and struggle for justice, egalitarianism and protect weak people. The methodology of this writing is qualitative research. In fact, Wahid’s thought of egalitarianism, tolerance, and liberalism influences the young generation of NU organization that creates a thought of school, namely post-radisionalist (Postra). Postra is a kind of leap thought among NU generation that carries out themes, such as, egalitarianism, tolerance, liberalism, civil society, and democracy. In South Sulawesi, the NU young generation establishes a non-government organization (NGO), which is called Lembaga Advokasi Pendidikan Anak Rakyat that carries out the same theme that of Wahid’s.Keywords: Abdurahman Wahid; Nahdlatul Ulama; Islamic Post-Traditionalist: LAPAR organization: الملخصتوضح هذه المقالة أفكار عبد الرحمن وحيد وتأثيرها في خلق وجهة النظر الجديد للتفكير جيل الشباب في  النهضة العلماء (NU) بإندونيسيا. تطبق هذه المقالة تقنيات نوعية من خلال الدراسة المكتبية  والمجال البحثي النوعي والمصادر الرئيسية لها عبارة عن مجموعة من طرق إجراء الاستطلاعات  بحيث تم العثور على بياناتها الأساسية من خلال المراقبة والمقابلات والتوثيق ، وأما مصادرها أو مراجعها الثانوية  فهي تستمد من الكتب المدرسية والمجلات العلمية والإنترنت، فقد تم تحليل البيانات المذكورة باستخدام المنهج التحليلي. ومن العروف أن  "NU"  إسلامية تقليدية، وبينما يعرف أن  المحمدية هي  إسلامية حديثة. ويريد عبد الرحمن وحيد أن يكون المجتمع المسلم مجتمعا صالحا يتحلى بكل من صفات الخير كالتسامح والاحترام للآخرين. وينبغي لكل مسلم أن يحترم الآخرين وأن يسعى إلى إقامة العدالة والمساواة وحماية الموطنين الضعفاء.  وفي الواقع، أن أفكار وحيد المائلة إلى التساوى التسامح والليبرالية والتي تؤثر على الجيل الناشئ منNU تمثل خطوات فكرية لدى هذا الجيل الذي يحمل مواضيع مختلفة كالمساواة والتسامح، والحرية، والديمقراطية. وفي سولاويسي الجنوبية ،أنشأ هذا الجيل  غير حكومية أطلقت عليها اسم المؤسسة الخيرية ويقال لها مؤسسة المحاماة لدعم تعليم أبناء الشعب (LAPAR) وهي المؤسسة التي تحمل نفس الموضوع مثل ما دعى به وحيد)الكلمة الرئسية: عبد الرحمن وحيد؛ نهضة العلماء؛ آخر- التقليدية؛ LAPAR؛ Abstrak Tulisan ini menggambarkan pemikiran Abdurrahman Wahid dan pengaruhnya dalam menciptakan paradigma baru pemikiran generasi muda organisasi Nahdlatul Ulama (NU) di Indonesia. Tulisan ini mengaplikasikan teknik kualitatif melalui penelitian pustaka dan lapangan. Data primer diperoleh melalui observasi, wawancara, dan dokumentasi, sementara sumber sekunder diperoleh melalui buku teks, jurnal ilmiah dan internet. Data-data tersebut dianalisis melalui analisis deskriptif. Organisasi NU adalah diketahui sebagai organisasi Islam tradisionalis sementara organisasi Muhammadiyah dikenal sebagai organisasi Islam modernis. Wahid ingin integritas Muslim menjadi masyarakat yang baik, seperti toleran dan hormat kepada orang lain. Setiap Muslim harus menghargai orang lain dan berjuang untuk menegakkan keadilan, egalitarian, dan melindungi penduduk yang lemah. Dalam kenyataannya, Pemikiran Wahid yang berkarasteristik egaliter, tolerans, dan cenderung liberal memengaruhi generasi muda NU adalah sebuah loncatan berpikir sepanjang generasi muda NU yang mengusung tema seperti egaliterian, toleran, liberal, civil society, dan demokrasi. Di Sulawesi Selatan, generasi muda NU mendirikan sebuah Lembaga Swadaya Masyarakat (LSM) yang disebut dengan nama Lembaga Advokasi Pendidikan Anak Rakyat (LAPAR) yang mengusung tema yang sama dengan Wahid.Kata Kunci: Abdurahman Wahid; Nahdlatul Ulama; Islam Post-Traditionalis: organisasi LAPAR: